Characterization of the complete chloroplast genome of Pterocarya macroptera var. delavayi (Juglandaceae). Issue 4 (3rd April 2021) - Yan, Hua; Zhang, Jisi; Ye, Jianfei; Guo, Chunce; Xiang, Xiaoguo
Abstract: In this study, the complete chloroplast genome sequence of Pterocarya macroptera var. delavayi was reported and characterized. The chloroplast genome is 160, 168 bp in length, and consists the typical quadripartite structure, a pair of inverted repeats (IRs, 26, 007 bp) separated by a large single-copy region (89, 701 bp) and a small single-copy region (18, 453 bp). A total of 136 unique genes were predicted, including 88 protein-coding genes, 40 tRNA genes, and 8 rRNA genes. The GC content of the chloroplast genome is 36.2%. Phylogenetic analysis confirmed the close relationship between Pterocarya and Juglans .